The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/md.0000000000027902
|View full text |Cite
|
Sign up to set email alerts
|

Fast and precise pathogen detection and identification of overlapping infection in patients with CUTI based on metagenomic next-generation sequencing

Abstract: Rationale: The gold standard for pathogen detection and identification of complicated urinary tract infection (CUTI) remains quantitative urine culture, however, the diagnostic value of urine culture remains limited due to the time-consuming procedure and low detection rate. Here we report a case of successfully using Metagenomic next-generation sequencing (mNGS) provided fast and precise detection and identification of overlapping infection in patients with CUTI with no similar reports or studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Clinically, complicated UTIs are defined as those associated with factors that compromise the urinary tract or host defense, including urinary tract obstruction, immunosuppression, renal failure, and foreign bodies such as indwelling urinary catheters or other drainage devices (Lichtenberger and Hooton, 2008;Levison and Kaye, 2013). In our cases, the majority of patients had complicated UTI that showed recurrent, persistent and refractory features similar to the previous reports (Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Clinically, complicated UTIs are defined as those associated with factors that compromise the urinary tract or host defense, including urinary tract obstruction, immunosuppression, renal failure, and foreign bodies such as indwelling urinary catheters or other drainage devices (Lichtenberger and Hooton, 2008;Levison and Kaye, 2013). In our cases, the majority of patients had complicated UTI that showed recurrent, persistent and refractory features similar to the previous reports (Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 76%
“…The applications of mNGS on non-sterile materials (e.g., urine) remains are still scarce and controversial. In one of the few recent studies on urine (Zhang et al, 2021;Zhang et al, 2022), a prospective proof-ofconcept study by Janes, V. A and colleagues confirmed the feasibility of metagenomic sequencing in detecting of urinary pathogens and drug resistance (Janes et al, 2022). We conducted a mNGS study in patients with suspected UTI and compared it with conventional test in terms of diagnostic performance, pathogenic findings to demonstrate its significance.…”
Section: Discussionmentioning
confidence: 95%
“…Metagenomic techniques were used to successfully identify pathogens directly from patient specimens, including cerebrospinal fluid, 13 , 17-25 respiratory secretions, 26-31 skin and soft tissue or bone and joint tissues/synovial fluid, 32 , 34 heart valve tissue, 35 and urine. 36 A review of the methods sections revealed significant heterogeneity in sensitivity and specificity of testing due to variability in study design, reference standards, clinical factors, and technical variation among the laboratories performing the testing. For exemplar US publications, laboratories of the University of California at San Francisco were featured prominently as testing laboratories.…”
Section: Resultsmentioning
confidence: 99%